Literature and nursing: sources and knowledge for research in history - Taka Oguisso; Onã Silva (Universidad de Alicante, 2017)
As a profession, nursing needs to define its humanitarian character and the caring culture through literature in support of its professional identity. Objectives: a) to present historical data of publications on nursing within literature of Brazilian and foreign authors; b) to identify contemporary nurses with production and publication in the literature field; c) to reflect on the interfaces between literature and nursing as humanistic knowledge for the caring art. Method: historical study based on documentary analysis of literary works. Primary sources were literary works published by Brazilian or by foreign writers referring to nursing or nurses. Outcomes: After reading the literary texts by selected writers, were drawn out dialogues, texts or information related to nursing or the nurse's job performed by the fictitious characters created by the writers. Conclusion: In fact, literature as an art and effective knowledge field for nursing studies and researches deserves more attention due to the humanistic, philosophical and more inclusive vision and the new look not addressed only to the world of contemporary sophisticated technology of the profession.